KONSISTENSI KEBIJAKAN EKONOMI DALAM HUKUM DAN IMPLIKASINYA TERHADAP PERTUMBUHAN SEKTOR USAHA DI INDONESIA - Sri Jekan Anggun Bandu; Delma Iren Bandu (Fakultas Hukum Universitas Kristen Indonesia, 2026)
In the context of legal policy in Indonesia, consistency in economic policy and public welfare is a major concern in supporting business sector growth. This study explores two main approaches in legal policy: the public welfare approach, which focuses on improving the overall standard of living of the community, and the business sector growth approach, which emphasizes the distribution of opportunities and the protection of individual rights. The methodology used is qualitative with a descriptive-analytical approach, including literature studies, legal document analysis, and data analysis. The results of the study show that although various policies have been implemented to improve public welfare, challenges remain, such as a lack of coordination between institutions and limited budgets. These two approaches complement each other, whereby effective policies must be able to integrate the principles of justice and economic growth. This study concludes that the realization of justice and business sector growth in Indonesia needs to be carried out through efforts to distribute resources evenly and pay attention to disadvantaged groups in society, in order to create more equitable and sustainable welfare.